2011
DOI: 10.1080/09540121.2011.565027
|View full text |Cite
|
Sign up to set email alerts
|

Sexual risk taking and club drug use across three age cohorts of HIV-positive gay and bisexual men in New York City

Abstract: This study examined club drug use, (i.e., cocaine, ecstasy, ketamine, GHB, and methamphetamine) and unprotected anal intercourse (UAI) in an ethnically and racially diverse sample of 166 New York City-based seropositive, club drug-using, gay and bisexual men, ages 19 to 61, and considered these behaviors in relation to age category (20s, 30s, 40+) and number of years living with HIV. Club drug use was common across all age categories, with differences arising only in the type of club drug used. Multivariate lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 26 publications
5
39
1
Order By: Relevance
“…We found no significant association between HIV status and stimulant drug use or poly-drug use in bivariate and multivariate analyses. This would seem to be at odds with research that has found such a link (e.g., Gorman et al, 2004; Pappas & Halkitis, 2011; Stall et al, 2001; Vaudrey et al, 2007); it should be noted that our confidence intervals did include the effects noted in the literature. While statistically significant associations have generally been found among MSM samples which include large numbers of white men, it may be that this relationship differs with exclusively ethnic minority MSM samples.…”
Section: Discussioncontrasting
confidence: 67%
“…We found no significant association between HIV status and stimulant drug use or poly-drug use in bivariate and multivariate analyses. This would seem to be at odds with research that has found such a link (e.g., Gorman et al, 2004; Pappas & Halkitis, 2011; Stall et al, 2001; Vaudrey et al, 2007); it should be noted that our confidence intervals did include the effects noted in the literature. While statistically significant associations have generally been found among MSM samples which include large numbers of white men, it may be that this relationship differs with exclusively ethnic minority MSM samples.…”
Section: Discussioncontrasting
confidence: 67%
“…Numerous studies have documented associations between drug and alcohol use and HIV transmission risk (Colfax et al, 2004); (Koblin, Chesney, Husnik, et al, 2003b; Mayer, Wang, Koblin, et al, 2014; Ostrow, Plankey, Cox, et al, 2009; Pappas & Halkitis, 2011; Sander, Cole, Stall, et al, 2013; Skeer, Mimiaga, Mayer, et al, 2012). However, MSM subpopulations are not homogenous and often exhibit different substance-use related risk profiles (Newcomb, Ryan, Greene, et al, 2014).…”
mentioning
confidence: 99%
“…HIV status, relationship status, and age were controlled in the analyses predicting UAI given past reports linking these factors to condom use. 7,12,[22][23][24][25][26] We did not formulate a specific hypothesis about the amount of pleasure loss associated with condoms for the insertive position compared to the receptive position, as complaints about condoms inhibiting physical sensation and interfering with emotional connectedness have been voiced from both stances. With regard to our second objective, we hypothesized that greater perceived pleasure loss would be related to a higher likelihood of UAI in both positions.…”
mentioning
confidence: 99%